1992
DOI: 10.1007/bf00179379
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects and distribution of immunologically active cells in the nasal mucosa of patients with nasal polyps after endoscopic sinus surgery and treatment with topical corticosteroids

Abstract: Clinical parameters of 72 patients who were operated upon for nasal polyps were evaluated as well as biopsy specimens of the mucosa of the middle and inferior turbinates of 41 of these patients. Biopsies were taken at the time of endoscopic sinus surgery (ESS), after 6 months and after 1 year in 23 patients. During the follow-up period the patients were treated with topical corticosteroids (budesonide). At the time of ESS significantly more CD8+ (suppressor/cytotoxic) cells than CD4+ (helper/inducer) cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
1
28
0
1
Order By: Relevance
“…Eosinophil infiltration is a striking feature of nasal polyps: eosinophils are markedly more numerous in most nasal polyps than in the mucosa of the middle and inferior turbinates (Bernstein et al, 1995;Stoop et al, 1992Stoop et al, , 1993. Increased numbers of macrophages and other lymphocytes are also observed in nasal polyps as compared with normal nasal mucosa (Bernstein et al, 1995;Stoop et al, 1992Stoop et al, , 1993. These types of inflammatory cells, particularly eosinophils because of their large majority, increase A, schematically illustrates the trajectories of two cells with different types of behavior pattern.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Eosinophil infiltration is a striking feature of nasal polyps: eosinophils are markedly more numerous in most nasal polyps than in the mucosa of the middle and inferior turbinates (Bernstein et al, 1995;Stoop et al, 1992Stoop et al, , 1993. Increased numbers of macrophages and other lymphocytes are also observed in nasal polyps as compared with normal nasal mucosa (Bernstein et al, 1995;Stoop et al, 1992Stoop et al, , 1993. These types of inflammatory cells, particularly eosinophils because of their large majority, increase A, schematically illustrates the trajectories of two cells with different types of behavior pattern.…”
Section: Discussionmentioning
confidence: 96%
“…As stated by Bernstein et al (1995), various hypotheses have been proposed to explain the cause of nasal polyps, with the two most plausible and widely discussed theories being allergy and inflammation. Eosinophil infiltration is a striking feature of nasal polyps: eosinophils are markedly more numerous in most nasal polyps than in the mucosa of the middle and inferior turbinates (Bernstein et al, 1995;Stoop et al, 1992Stoop et al, , 1993. Increased numbers of macrophages and other lymphocytes are also observed in nasal polyps as compared with normal nasal mucosa (Bernstein et al, 1995;Stoop et al, 1992Stoop et al, , 1993.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highest levels of IL-8 and the highest percentages of lavage neutrophilia were seen in subjects classified as "nonallergic." In contrast, patients with chronic rhinosinusitis and associated allergic rhinitis had a modestly increased percentage of neutrophils and elevated IL-8 levels in the lavage fluid [30,31]. In a related study [32], increases in IL-8 were found by quantitative competitive PCR in sinus tissue obtained at the time of sinus surgery.…”
Section: Discussionmentioning
confidence: 92%